(3TQM bWQ GdfOi hHd GdUOis - (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, J (B761 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMeO ddg QGaY GdOQLGJ s
(3BNQgG (B:s
(3Efg GdLhGO GdcQje GdQDha GdQMje hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH GdeJf HGdeOGO GdCMeQs
(3hYdjg Jedc ddSjO eMeO eMi GdOjf Hf eMeO GdTgjQ HGHf GdNQGW SfI (B1156 (3g` s
(3JHUQI GdYfhGf (B:s
(3TQM s
Keywords: (3GdfMhs